Sweetening K-channels: what sugar taught us about permeation and gating - Naranjo, David; Diaz-Franulic, Ignacio (Frontiers in Molecular Biosciences, 2023)
Because they enable for the modification of both viscosity and osmolarity, sugars have been used as a biophysical probe of voltage-gated K-channels for a while. Viscosity variations made it possible to measure the pore sizes in large and small conductance K-channels using techniques similar to those used in the 1980s to study the gramicidin A channel. These analyses led to the finding that the size of the internal mouth appears to be the primary cause of the conductance differences between Shaker-like channels and large conductance BK-channels. As an osmotic agent, adding sugar unilaterally causes streaming potentials that indicate H2O/K+ cotransport across the BK-channel pore. Osmotic experiments on Shaker K-channels suggest that the pore gate operation and the slow inactivation displace comparable amounts of water. Functionally isolated voltage sensors allow estimation of individual osmotic work for each voltage sensing charge during voltage-activation, reporting dramatic internal and external remodeling of the Voltage Sensing Domain´s solvent exposed surfaces. Remarkably, each charge of the VSD appears to take a unique trajectory. Thus, manipulation of viscosity and osmolarity, together with 3D structures, brings in solid grounds to harmonize function and structure in membrane proteins such as K-channels and, in a wider scope, other structurally dynamic proteins.